2016
DOI: 10.5714/cl.2016.17.1.074
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an inorganic ammonium salt treatment on the flame-retardant performance of lyocell fibers

Abstract: Lyocell fibers are produced by dissolving cellulose in a N-methylmorpholine-N-oxide/ water solution. The resulting cellulose/N-methylmorpholine-N-oxide/water mixture is extruded through an orifice, drawn into an air gap, and then precipitated in a coagulation bath [1]. In contrast with rayon fibers, lyocell fibers have higher tenacity, a higher modulus, lower shrinkage when dried, and lower reductions of tenacity and the modulus when wet. Moreover, lyocell fibers are round and have molecular chains that are hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 15 publications
(36 reference statements)
0
5
0
Order By: Relevance
“…The main decomposition step of the control sample occurred at 280-380 C, either under air or nitrogen atmosphere, involving the degradation of cellulose molecular chains and the generation of fatty coke. 6 The weight loss was 71.18% and 77.65% under air and nitrogen atmospheres, and the maximum weight loss rates were reached at 323 C and 338 C, respectively. The residual char of the fabric was further decomposed above 380 C in which some of the aliphatic coal coke was converted to aromatic coal coke.…”
Section: Thermal Stabilitymentioning
confidence: 91%
See 1 more Smart Citation
“…The main decomposition step of the control sample occurred at 280-380 C, either under air or nitrogen atmosphere, involving the degradation of cellulose molecular chains and the generation of fatty coke. 6 The weight loss was 71.18% and 77.65% under air and nitrogen atmospheres, and the maximum weight loss rates were reached at 323 C and 338 C, respectively. The residual char of the fabric was further decomposed above 380 C in which some of the aliphatic coal coke was converted to aromatic coal coke.…”
Section: Thermal Stabilitymentioning
confidence: 91%
“… 5 Blend spinning refers to mixing a suitable flame retardant with a spinning solution, then the resulting spinning solution is introduced into a coagulation bath through the spinneret, and then the flame retardant fiber is prepared by drawing. 6 Delholm et al mixed organically modified montmorillonite nanoparticles into a cotton cellulose/NMMO solution to significantly increase the char residue of the resulting regenerated cellulose during the combustion process. Specifically, when the clay additive was 15%, the residual char increased to 30%.…”
Section: Introductionmentioning
confidence: 99%
“…Bai and Kim et al used inorganic salts as flame retardants to study the influence of several different inorganic salts on the flame retardancy of Lyocell fiber and found that the amount of carbon residue of the fiber increased with a higher content of flame retardant. [ 14–16 ] The presence of carbon residue inhibits the diffusion of combustion gases into the pyrolysis zone and therefore protects the material surface from the influence of heat and air. Hall et al prepared flame‐retardant Lyocell fibers by using N‐methylol dimethylphosphonopropionamide (Pyrovatex CP) as a flame retardant.…”
Section: Introductionmentioning
confidence: 99%
“…For the issue of environmental protection, wet-spun cellulose fibers derived from green solvent were first studied in the early1980s [1]. Lyocell fibers are fabricated by first dissolving cellulose in N-methylmorpholine-N-oxide/aqueous solution to form an even spinning solution, then it was extruded through a spinneret, and immersed into a coagulation bath to form lyocell fibers by drawing [2]. Compared with the traditional viscose process, the production of lyocell fibers is a simple and resource-saving method for the production of regenerated cellulose fibers [3].…”
Section: Introductionmentioning
confidence: 99%